2018
DOI: 10.1021/acs.jpcc.8b08594
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cations in Adsorption of Supercritical Carbon Dioxide at Smectite Mineral–Water Interfaces: Molecular Dynamics and Adaptive Biasing Force Simulation Studies

Abstract: The microscopic understanding of uptake and retention of supercritical carbon dioxide by expandable layered aluminosilicate minerals is of central importance for large-scale geological sequestration of CO2. At the molecular scale, the interlayer charge-balancing cations (CBCs) play a crucial role in CO2 adsorption by these cost-effective and environmentally friendly materials. This article investigates the influence of CBCs on the structure, dynamics, and energetics of CO2–H2O mixtures nanoconfined in four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 132 publications
2
11
0
Order By: Relevance
“…For example, the presence of CO 2 and CH 4 hardly affects the distribution of the interlayer water and ions in these systems. ,,,,,,,,,,,,,, The distribution of CO 2 and CH 4 normal to the clay surface shows layered structures similar to those observed, for example, for water. In general, the in-plane distributions of the interlayer water and ions almost coincide and they were positioned in mutually exclusive regions with CO 2 and CH 4 . ,,,,, The isosteric heat of adsorption of CO 2 was higher than that of CH 4 , which agrees with the higher uptake of CO 2 . , The RDFs provide insights into the interactions of the ion–water–clay system with CO 2 and CH 4 . ,,,,, ,,, For example, as hydration/RH increases, CO 2 ,,,, and CH 4 , lose coordination to surface oxygens and become more fully solvated to water molecules. It was shown that CO 2 hardly migrates into the first hydration shell of the strongly hydrated interlayer ions (Figure ).…”
Section: Adsorption Of Carbon Dioxide Methane and Their Mixture In Sw...mentioning
confidence: 73%
See 4 more Smart Citations
“…For example, the presence of CO 2 and CH 4 hardly affects the distribution of the interlayer water and ions in these systems. ,,,,,,,,,,,,,, The distribution of CO 2 and CH 4 normal to the clay surface shows layered structures similar to those observed, for example, for water. In general, the in-plane distributions of the interlayer water and ions almost coincide and they were positioned in mutually exclusive regions with CO 2 and CH 4 . ,,,,, The isosteric heat of adsorption of CO 2 was higher than that of CH 4 , which agrees with the higher uptake of CO 2 . , The RDFs provide insights into the interactions of the ion–water–clay system with CO 2 and CH 4 . ,,,,, ,,, For example, as hydration/RH increases, CO 2 ,,,, and CH 4 , lose coordination to surface oxygens and become more fully solvated to water molecules. It was shown that CO 2 hardly migrates into the first hydration shell of the strongly hydrated interlayer ions (Figure ).…”
Section: Adsorption Of Carbon Dioxide Methane and Their Mixture In Sw...mentioning
confidence: 73%
“…The molecular dynamics (MD) simulations allow one to assess the dynamic properties of the system. For the simulations of the clay systems, the structure of the unit cell of the clay (Si 8 Al 4 O 20 (OH) 4 ) is obtained from, for example, Skipper et al The simulations mainly focus on the low-charge (Wyoming-type) montmorillonite M 0.75/ n (Si 8 )­(Al 3.25 Mg 0.75 )­O 20 (OH) 4 , where M represents a counterion (e.g., Li + , Na + , K + , Mg 2+ , Ca 2+ , or Sr 2+ ) and n is the charge on the ion. This clay contains coordinated tetrahedral silica sheet and octahedral alumina sheet forming 2:1 tetrahedral-octahedral-tetrahedral (TOT) layers.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations